The Use of β-blockers in Patients with Ventricular Ectopic Heartbeat in the Early and Distant Postinfarction Period - N. M. Kulayets (Zaporožskij Medicinskij Žurnal)
Aim: to increase the effectiveness of patients after Q-, QS- myocardial infarction rehabilitation, based on the study of clinical, instrumental and biochemical changes in cases of cardiac arrhythmias, and development on this basis of new approaches to treatment.